What will surgical coronary revascularization look like in 25 years?. (November 2019) - Caliskan, Etem; Emmert, Maximilian Y.; Falk, Volkmar
Abstract : Purpose of review: Coronary artery bypass grafting evolved in incremental but significant steps since its introduction. Here, we provide an update on operative techniques, choice of conduits, patient selection/decision-making and primary and secondary prevention measures with potential of influencing the future of coronary artery bypass grafting (CABG) surgery. Recent findings: Associated mortality of off-pump CABG (OPCAB) procedures performed in high-volume OPCAB centers (≥164 cases per year) and by experienced surgeons (≥48 cases per year) was reduced compared with on-pump CABG with two or more grafts suggesting a volume-based dependency of outcomes in CABG procedures with high-technical complexity. Ten-year results from the recent Arterial Revascularization Trial showed no significant between-group difference for the primary and secondary outcome. Total arterial revascularization using composite bilateral internal mammary artery-Y-conduits through a limited access mini-thoracotomy was not only shown to be feasible but a safe and reproducible procedure with excellent midterm outcomes. The most recent Randomized Trial of Endoscopic or Open Vein-Graft Harvesting for Coronary-Artery Bypass (REGROUP) trial demonstrated no significant difference between open vein-graft harvesting and endoscopic vein-graft harvesting in the occurrence of major adverse cardiac events. Summary: Adherence to the most recent guidelines on myocardial revascularization is a key component for providing state-of the CABG surgery. Trends to lesser invasiveness in surgical coronary revascularization will gain momentum and is expected – with further improvements – to be the mainstay of future surgical coronary revascularization strategies.